Nutrition of draught oxen in semi-arid West Africa. 3. Effect of body condition prior to work and weight losses during work on food intake and work output - Fall, Abdou; Pearson, R.A.; Fernández Rivera, S. (Cambridge University Press, 1997)
Eighteen oxen were allotted to three treatment groups according to their body condition: poor, medium and good. Work output, speed, live weight and body condition were measured during 7 weeks when animals worked 4 days/ week, 4 h/day, pulling loads equivalent to 12.5 kg/100 kg live weight. The animals were given millet stover ad libitum during hours they did not work plus 10 g/kg M of a concentrate mix. Work did not influence intake of millet stover. However, food intake improved as work progressed and animals in bad condition ate more millet stover than animals in good body condition. Work performance was affected by live weight but not body condition. Live-weight losses did not have a deterimental effect on work performance. Power output improved during the course of the experiment while animals were losing weight Animals in all treatment groups lost body weight during the 7 weeks of work but weight losses were more pronounced in oxen in good than in poor body condition. At the end of the working period, animals were put on natural pastures without supplementation. It took 4 weeks for animals in poor and medium body condition and 6 weeks for animals in good body condition to reach their pre-work live weight.